2005
DOI: 10.1152/ajpregu.00837.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral and systemic hemodynamic changes during cognitive and motor activation paradigms

Abstract: Cognitive and/or sensorimotor stimulations of the brain induce increases in cerebral blood flow that are usually associated with increased metabolic demand. We tested the hypothesis that changes in arterial blood pressure (ABP) and arterial Pco(2) also take place during brain activation protocols designed to induce hemispheric lateralization, leading to a pressure-autoregulatory response in addition to the metabolic-driven changes usually assumed by brain stimulation paradigms. Continuous recordings of cerebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
89
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 37 publications
13
89
0
Order By: Relevance
“…The method based on the analysis of TCD and ABP waveform was introduced to calculate CCP noninvasively in various clinical conditions Moody et al, 2005;Edouard et al, 2005). In our study, we confirmed a significant correlation between the values of CCP derived from TCD waveform (noninvasive) and that calculated from cardiac arrest (CCP LDF and CCP TCD ; invasive).…”
Section: Discussionsupporting
confidence: 81%
“…The method based on the analysis of TCD and ABP waveform was introduced to calculate CCP noninvasively in various clinical conditions Moody et al, 2005;Edouard et al, 2005). In our study, we confirmed a significant correlation between the values of CCP derived from TCD waveform (noninvasive) and that calculated from cardiac arrest (CCP LDF and CCP TCD ; invasive).…”
Section: Discussionsupporting
confidence: 81%
“…Scholkmann et al (2013) showed that PaCO 2 changes were evoked by speech and mathematical tasks, and strongly affected the fNIRI signals. Task execution may also lead to significant changes in BP during certain experimental tasks such as arm-rising (Minati et al, 2011), anagram task (Tachtsidis et al, 2008a(Tachtsidis et al, ,c, 2009), word generation and constructional puzzle task (Moody et al, 2005), semantic continuous performance task (Jelzow et al, 2011), or emotional picture presentation (Minati et al, 2009). These BP changes affect hemodynamics in the extracerebral compartment, measured as stimulus/task-related changes in SBF and/or volume (SBV) (Kirilina et al, 2012;Takahashi et al, 2011), or even in the cerebral compartment itself (Minati et al, 2011 Another source of systemic component is the influence of the autonomic nervous system (ANS) on the cerebral vasculature (Hamel, 2006;Wahl and Schilling, 1993).…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…[65][66][67] Using this approach, a number of interesting studies have been completed with the following conclusions: (1) hypercapnia impairs the metabolic regulation of neurovascular coupling, (2) breath-bybreath changes in ETCO 2 during cognition can impact the neurovascular coupling response, and (3) the blood pressure response to cognitive activation plays a large role in the neurovascular coupling response, particularly the initial spike. 53,66,68 These interesting studies have yet to confirm a direct mechanistic link between the physiological regulatory pathways of interest (i.e., metabolic versus myogenic influences) and the subcomponent models/metrics being utilized (i.e. critical closing pressure versus resistance area product).…”
Section: Human Neurovascular Couplingmentioning
confidence: 99%